Fire on ice: the story of Icelandic Latter-day Saints at home and abroad - Woods, Fred E. (Religious Studies Center, Brigham Young University, 2005)
The setting -- The restored gospel comes to Iceland -- Immigration to Utah and early settlement of Spanish Fork -- Life in Spanish Fork and other Utah regions -- Gathering converts from Iceland (1873-1914) -- Gospel messengers return to Iceland -- The church in Iceland today (1977-present) -- Epilogue : joining hands across the water